With a Little Help from My Mother. The Matrilineal Advantage in European Grand Parenting - Giorgio Brunello; Eiji Yamamura (Institute of Labor Economics (IZA), 2021)
This study documents the matrilineal advantage in grandparent – grandchildren relationships in Europe, using data on 20 European countries and Israel from the Survey of Health, Ageing and Retirement (SHARE). We show that maternal grandparents look after grandchildren and provide financial or material gifts to children more than paternal grandparents do. In exchange, daughters help their parents with personal care, household tasks and paperwork more than sons do. The matrilineal advantage is stronger for grandmothers than for grandfathers, and stronger in the more conservative societies of Southern Europe, where gender inequality is higher and trust in others is lower.
Keywords: J12; J13; 330; childcare; Europe; family